A school excursion to a museum can promote physical activity in children by integrating movement into curricular activities. (February 2019) - Mygind, Lærke; Kryger, Tine; Sidenius, Gry; Schipperijn, Jasper; Bentsen, Peter
Since children spend a large proportion of their time in institutional settings such as schools, health promotion researchers have identified this as an important setting to promote physical activity (PA). Apart from physical education, PA could be integrated into the school curriculum in other ways. Therefore, the aim of this study was to examine whether a school excursion to a museum can increase primary school students' PA and reduce sedentary time. One hundred and ten primary school students aged 12–13, from three Danish schools, wore accelerometers for four consecutive days, of which one consisted of an excursion day to a museum. While an increase in light physical activity and reduction in the amount of sedentary time was observed, students did not spend more time in moderate to vigorous PA (MVPA) during the visit to the museum than on a regular school day. However, over the full excursion day, the students accumulated more MVPA. One school used active transportation to and from the museum, which contributed to significantly more MVPA compared to the other schools. An excursion to a museum significantly reduced sedentary time, but was in itself not sufficient to increase MVPA.